WISATA BAHARI PADA ZONA PEMANFAATAN TAMAN NASIONAL MANUSELA: POTENSI DAN FAKTOR PENGARUH PENGEMBANGAN - Ivonne R. Kaya; Fildo de Lima (Universitas Pattimura, 2019)
Tourism has become one of the major players in ‎international commerce and represents one of the main income ‎sources for many developing countries at the same time. These dynamics have turned tourism into a key driver for socio-‎economic progress.‎ This article described the potential of tourism attraction and factor affecting the development of marine tourism area in the utilization zone of Manusela National Park. Semi-structured interviews, in-depth interviews and participant observations were conducted with respondent (n=110) in Bellarizky, Air Belanda, Ora Beach and Lizar Bahari resort. The potential of tourist attractions in the utilization zone of Manusela National Park is as a snorkeling, diving and point of view. Factors affecting the development are service, transportation, supporting facilities and tourism attractions.